THE RELATIONSHIP BETWEEN ENGAGEMENT AND BURNOUT AMONG STUDENT IN UNIVERSITI MALAYSIA SABAH (UMS) - Chen Kaiyue (Malaysian Journal of Business and Economics (MJBE), 2022)
This study investigated the relationship between engagement and burnout of students at Universiti Malaysia Sabah (UMS). This study found that there is indeed a significant negative correlation between engagement and burnout. Among them, the assumption of engagement, vigor and engagement is not accepted, and the relationship between them is not very significant. But the relationship between dedication and absorption, these two factors and engagement is very significant. They have a huge impact on engagement. For burnout, the study found that exhaustion, cynicism and effectiveness are closely related to burnout, and these three factors will have a significant impact on burnout. Finally, this study shows that in order to improve the learning attitude of UMS students, UMS managers and lecturers should find ways to mobilize students’ dedication and absorption to improve students’ engagement and reduce burnout, and find ways to control students’ exhaustion, cynicism and Efficacy to build a positive learning atmosphere.